Otwarta nauka i (nie)bibliometryczne aspekty ewaluacji : 15. Seminarium Open Access w Bibliotece Uniwersytetu Łódzkiego, 22 października 2024 - Zatora, Anna (Zagadnienia Rodzajów Literackich, 2024)
The text is a report on the 15th Open Access Seminar at the University of Lodz Library (2024, October 22). For the fifteenth time, the University of Lodz is organizing the Open Access Seminar as part of the International Open Science Week. For more than a dozen years, the University of Lodz has been inviting the academic community to discuss topics that are key to the development of the idea of open science in Poland, and in 2024 the place of open science in the evaluation and assessment of scientific activity was considered such a topic. In this connection, a panel discussion was organized at the Library of the University of Lodz with the participation of experts: Ewa Bluszcz, Andrzej Jajszczyk, Stanisław Kistryn, Katarzyna Anna Nawrot, Krzysztof Pabis, Magdalena Wnuk. The discussion was moderated by Jarosław Płuciennik. Such topics as the absence of open science in evaluation, non-bibliometric aspects of evaluation of scientific activity, discipline specifics and evaluation criteria, nitiatives for improving the system of science evaluation (especially Coalition for Advancing Research Assessment: CoARA), possible directions for the development of the Polish system of evaluation of science and scientists were discussed. According to participants in the event, the Polish evaluation system has not worked and needs to be changed. It would be worthwhile to incorporate CoARA’s demands, as well as to involve scientists themselves more in efforts to improve the evaluation system.